INTRODUCTION TO PLANT BIOCHEMISTRY - GOODWIN, T.W.; MERCER, E.I. (New Delhi CBS Publishers, 2003)
This text provides readers with an in-depth exploration of how biological control functions and how it can be safely employed to solve pest problems and enhance nature conservation. It covers the principles behind biological control techniques and their implementation and incorporates practical examples from the biological control of a variety of pests. It contains detailed chapters on conserving natural enemies through environmental management importation of new natural enemies for control of pests augmentation of natural enemies through rearing and release and the development and application of pathogens as biopesticides. The volume features a special chapter on techniques for evaluating the population effects of natural enemies on their target pests and new materials on frequently neglected aspect of biological control such as the influence of governmental policy the role of extension agents and the use of biological control for the conservation of native species and ecosystems. Biological Control is the only current text to provide students with a fundamental understanding of the subject along with the knowledge necessary for efficient implementation. It also offers environmentalists conservationists agriculturists and policy administrators an invaluable resource distinctive in its breadth of coverage and its integration of taxa.
https://www.cbspd.co.in/introduction-to-plant-biochemistry-2e
Keywords: Botany; Plant; Plant biochemistry